Tomato PHYTOCHROME B1 mutant responses to drought stress during vegetative and reproductive phases - Silva-Junior, Carlos Alberto [UNESP]; Alves, Frederico Rocha Rodrigues; Palaretti, Luiz Fabiano [UNESP]; de Oliveira, Reginaldo [UNESP]; Nascimento, Daniel Dalvan [UNESP]; Carvalho, Rogério Falleiros [UNESP] (Wiley, 2024)
Water availability is a limiting factor to plant development and productivity. Many drought-induced physiological processes that affect patterns of growth, biomass allocation, and ultimately, yield, are also regulated by the red/far-red photoreceptor phytochromes (PHYs). However, as the mechanisms and responses to drought stress vary among plant developmental phases, it is reasonable to conjecture that PHY-dependent morphophysiological responses to drought may be different according to the plant growth stage. In this study, we submitted tomato phyB1 mutant plants to water deficit in two distinct growth stages, during vegetative and flower-bearing reproductive phases, comparing the morphophysiological development, fruit yield and quality to wild-type (WT). In general, phyB1 plants overcome growth limitations imposed by water availability limitations during vegetative phase, being taller and leafier than WT. Restrictions to growth are less acute for both genotypes when water deficit occurs during reproductive phase compared to vegetative phase. phyB1 yield is lower when water is limited during reproductive phase, but its fruits accumulate more soluble solids, associated with better quality. These results highlight that drought-induced modulations in tomato growth and yield are dependent upon PHYB1 regulation and the developmental phase when water deficit is applied.
Keywords: biomass allocation; fruit quality; fruit yield; Solanum lycopersicum; water deficit